2016
DOI: 10.1097/pcc.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Admission Pao 2 and Mortality in Critically Ill Children: A Cohort Study and Systematic Review

Abstract: Hypoxia at admission is associated with increased mortality in critically ill children, whereas the association with hyperoxia is less clear. The cohort study demonstrated a U-shaped association between admission PaO2 and mortality. Further examination is needed to explore the effect of hyperoxia upon mortality prediction accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 35 publications
1
68
2
Order By: Relevance
“…Like others , we observed a tendency, although not statistically significant, for the SMR to be overestimated when the PaO 2 /FiO 2 ratio was omitted in the calculation of PIM2.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Like others , we observed a tendency, although not statistically significant, for the SMR to be overestimated when the PaO 2 /FiO 2 ratio was omitted in the calculation of PIM2.…”
Section: Discussionsupporting
confidence: 78%
“…Compared to previously published data, the proportion of arterial blood gases taken in this study was quite high (9,(11)(12)(13). We speculate that the high proportion of cardiovascular (including postoperative cardiac surgery) patients in the study with an arterial blood gas present is due to the fact that arterial cannulation in this group of patients often is required for haemodynamic monitoring and not primarily for gas exchange control.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…[3] We observed an excess mortality (both crude and adjusted) at extremes of oxygenation in 7410 critically ill children. [14] A complex Ushaped relationship between oxygenation and outcome is biologically feasible and may arise from the balance between harm from hypoxic injury at one extreme, and a combination of increased oxygen free radical damage and iatrogenic injury from more aggressive treatments at the other. [15] Clinical trials of oxygen targets in extremely premature infants have shown that they influence survival rates, retinopathy rates, and costs: large RCTs compared lower (85-89%) with higher SpO2 targets (91-95%).…”
Section: Resultsmentioning
confidence: 99%
“…Individual patient consent was not sought as this is a retrospective observational study and no patient identifiable data is reported . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Severe hypoxia is detrimental during critical illness, but hyperoxia has also been associated with adverse outcomes [1][2][3]. Harm from hyperoxia may be a biological consequence of oxidative damage or reflect iatrogenic injury resulting from more aggressive care.…”
mentioning
confidence: 99%